The Role of Islamic Education Teachers in Empowering Students’ Mental Health in The Post-Covid-19 Era - Darojatun Khasanah; M Nurul Ikhsan Saleh (Universitas Muhammadiyah Yogyakarta, 2023)
Motivated by the profound global impact of the Covid-19 pandemic on the education sector, specifically in elementary schools, a multitude of new policies have been implemented to address the challenges presented by online learning. Consequently, students often experience fatigue and a waning sense of enthusiasm, necessitating further adaptations amidst the ongoing pandemic. This research endeavours to investigate the efforts undertaken by Islamic education teachers to safeguard the mental health of students during this unprecedented era. The study primarily focuses on the perspectives of Islamic education teachers in elementary schools within the Cilacap district. Data was collected through in-depth interviews, observations, and examination of relevant documentation. The researchers employed various analytical techniques, including data reduction, data presentation, and verification of data conclusions, to scrutinize the research findings. The study underscores that Islamic education teachers possess a profound understanding of the vital importance of nurturing students' mental health. They assume a critical role in fostering well-being amidst the pandemic's trials and aftermath. These roles encompass acting as role models, providing constructive guidance, implementing engaging teaching methodologies, fostering effective communication between teachers and students' guardians, promoting positive habits, offering motivational praise, and employing disciplinary measures when necessary. The study concludes with recommendations for the government, educational authorities, and Islamic education teachers to integrate these aforementioned roles into their strategies, particularly at the elementary school level, to safeguard and promote students' mental health.